An amazing lesson on humility at IIUM - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
Raja Permaisuri Agong was appointed the university’s constitutional head (equivalent to the chancellor of a local university). The IIUM community is most fortunate to be reminded that “humility” is the hallmark of education in the Garden of Knowledge and Virtue. Therein humility is strongly advocated as the sign of a truly educated person.